Bridging the Gap between Physical Therapy and Orientation and Mobility in Schools: Using a Collaborative Team Approach for Students with Visual Impairments. (November 2017) - Szabo, Joanne; Panikkar, Rajiv K.
This article explores transdisciplinary collaboration and role-release strategies that would allow physical therapists and orientation and mobility (O&M) specialists to more effectively support students with visual impairments (that is, those who are blind or have low vision) and additional disabilities with their expanded core curriculum (ECC) goals. Through examining public and specialized school special education documentation for 20 school-aged students, the authors seek to better understand current practice patterns of both O&M and physical therapy professionals who are working with students who are visually impaired with additional disabilities, and suggest ways in which educational team members from both disciplines can work together toward common goals for their students.